High-borosilicic acid etching electromagnetic stove glass panel and preparation method thereof

CN122878043APending Publication Date: 2026-10-09ZHENGZHOU HIHO OPTICAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611129274.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0009]本发明要解决的技术问题是现有电磁炉玻璃面板触感生硬、耐温差不足、易划伤、易沾油污、厚度较大的技术问题,为解决上述问题,提供一种高硼硅酸蚀刻电磁炉玻璃面板及其制备方法

Benefits of technology

相对于现有技术,本发明提供的高硼硅酸蚀刻电磁炉玻璃面板采用3mm高硼硅玻璃作为基材,经特定酸蚀刻工艺处理,形成均匀的微观粗糙结构,微观粗糙结构的晶型为椭圆状蜂眼颗粒,粒径为10-30μm,粗糙度控制在1.0-1.3μm,使面板表面达到细腻柔滑、温润如玉的触感,解决了现有面板触感生硬的问题面板莫氏硬度≥6H,抗划伤性能优异,不易被钢丝球、刀具等划伤;表面水接触角≥105°,油接触角≥90°,耐油污性能好,油污易擦拭,无残留,延长面板使用寿命,电磁炉玻璃面板触感温润、性能优异、薄型化、可规模化量产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878043A_ABST
    Figure CN122878043A_ABST
Patent Text Reader

Abstract

The application provides a high-boron silicate etched glass panel for an electromagnetic cooker and a preparation method thereof, and belongs to the technical field of electromagnetic cooker accessories. The high-boron silicate etched glass panel for an electromagnetic cooker provided by the application adopts 3mm high-boron silicate glass as a base material, is processed through a specific acid etching process, forms a uniform micro rough structure, the crystal form of the micro rough structure is an elliptical honeycomb particle, the particle size is 10-30mu, the roughness is controlled to be 1.0-1.3mu, the surface of the panel reaches a delicate and smooth touch, and the problem of a hard touch of an existing panel is solved. The panel has a Mohs hardness of greater than or equal to 6H, excellent scratch resistance, and is not easy to be scratched by a steel ball, a knife and the like; the surface has a water contact angle of greater than or equal to 105 degrees, an oil contact angle of greater than or equal to 90 degrees, good oil stain resistance, easy wiping of oil stains, no residue, and a prolonged service life of the panel. The electromagnetic cooker glass panel has a warm touch, excellent performance, thinness, and can be mass produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of induction cooker accessories, specifically relating to a high borosilicate etched induction cooker glass panel and its preparation method. Background Technology

[0002] Induction cookers, as a highly efficient, energy-saving, and environmentally friendly kitchen appliance, are widely used in homes and restaurants. The glass panel, as a core component of the induction cooker, directly affects the user experience, safety, and lifespan. Currently, most induction cooker glass panels on the market use ordinary tempered glass or conventional borosilicate glass, with a thickness of 4-5mm, which presents the following technical challenges: 1. Stiff to the touch: Ordinary glass panels have a smooth surface, but feel cold and stiff to the touch, lacking warmth and resulting in a poor user experience.

[0003] 2. Insufficient resistance to temperature differences: Ordinary glass has a high coefficient of thermal expansion. Under the working conditions of an induction cooker, which heats up suddenly when turned on and cools down suddenly when turned off, it is prone to cracking and deformation, posing a safety hazard. Moreover, it is difficult to meet the thermal shock resistance requirements of an induction cooker.

[0004] 3. Poor scratch resistance: The surface hardness is low, making it easily scratched by steel wool, knives, etc. during use, affecting its appearance and service life.

[0005] 4. Easily attracts oil stains: The surface has no hydrophobic or oleophobic properties, so kitchen oil stains easily adhere to the surface and are difficult to wipe, affecting the cleanliness of the panel.

[0006] 5. Large thickness: Panels with a thickness of 4-5mm are relatively heavy and have poor adaptability, making it difficult to meet the development needs of mid-to-high-end induction cookers for thinner and lighter designs.

[0007] High borosilicate glass possesses excellent properties such as low coefficient of thermal expansion, high temperature resistance, impact resistance, and thinness, and has gradually replaced traditional soda-lime glass systems in the field of induction cooker panels. In 2025, its market penetration rate climbed to 58.4%. However, most existing high borosilicate glass panels do not undergo surface treatment or use simple frosting treatment, which still have problems such as poor tactile feel and poor oil resistance. Some panels using acid etching processes have problems such as poor etching uniformity, difficulty in controlling surface roughness, and unstable performance, which cannot meet the needs of mid-to-high-end induction cookers.

[0008] Prior art (CN 111362584 A) discloses a borosilicate glass etching solution, its preparation method, and its uses. The raw materials of the borosilicate glass etching solution include a mixed acid, a fluoride, a fluorosilicate, a surfactant, a soluble metal sulfate, a soluble metal hydrochloride, an intermediate filler, and water. The raw materials of the borosilicate glass etching solution can form stable complexes. The mixed acid includes sulfuric acid, nitric acid, phosphoric acid, and hydrochloric acid, and the surfactant is borax. This borosilicate glass etching solution can uniformly etch borosilicate glass and has good anti-glare effects, meeting the needs of the optoelectronic field. However, after etching borosilicate glass with this solution, the microscopic micron-sized particles on the surface are blocky or columnar particles, resulting in a low oil contact angle and lack of oil resistance, making it unsuitable for manufacturing induction cooker glass panels. Summary of the Invention

[0009] The technical problem to be solved by the present invention is that the existing glass panels of induction cookers have a hard touch, insufficient resistance to temperature differences, are easily scratched, easily get oil stains, and are too thick. In order to solve the above problems, a high borosilicate etched induction cooker glass panel and its preparation method are provided.

[0010] This invention is implemented in the following manner: A high borosilicate etched induction cooker glass panel, wherein the surface of the induction cooker glass is treated by an acid etching process to form a micro-rough structure, and the crystal form of the micro-rough structure is elliptical honeycomb-eye particles.

[0011] Preferably, the elliptical bee-eye particles have a particle size of 10-30 μm.

[0012] A method for preparing the above-mentioned high borosilicate etched induction cooker glass panel includes the following steps: 1) Substrate selection: High borosilicate glass was selected as the substrate; 2) Pretreatment: The borosilicate glass substrate to be treated is cleaned, dried, and degreased; 3) Preparation of etching solution: The etching solution is formulated by weight percentage as follows: hydrofluoric acid 8-12wt%, nitric acid 12-18wt%, citric acid 8-15wt%, ammonium fluoride 20-25wt%, sodium fluorosilicate 8-15wt%, starch 5-8wt%, potassium dihydrogen phosphate 1-3wt%, copper sulfate 2-6wt%, zinc chloride 2-6wt%, with the balance being water; weigh the raw materials in the formula and stir them evenly to obtain the etching solution, then place the pretreated borosilicate glass substrate into the etching equipment for etching; 4) Post-processing: The etched borosilicate glass substrate is cleaned and neutralized to remove residual etching solution from the surface, and then dried and annealed to obtain the finished panel.

[0013] Preferably, the thickness of the high borosilicate glass substrate in step 1) is 3-4 mm, and the coefficient of thermal expansion is 2.8 × 10⁻⁻⁻⁶. 6 / ℃ (20-300℃), flexural strength ≥65MPa, Vickers hardness ≥550HV, high temperature resistance ≥400℃, impact strength ≥120J / m², light transmittance ≥88%.

[0014] Preferably, the etching solution is formulated by weight percentage as follows: 8 wt% hydrofluoric acid, 15 wt% nitric acid, 12 wt% citric acid, 23 wt% ammonium fluoride, 10 wt% sodium fluorosilicate, 6 wt% starch, 2 wt% potassium dihydrogen phosphate, 4 wt% copper sulfate, 2.5 wt% zinc chloride, with the balance being water.

[0015] Preferably, the etching equipment in step 3) is a spray etching equipment, and the etching process parameters are: etching temperature 20-25℃, etching time 20-30min, and spray pressure 0.3-0.4MPa.

[0016] Preferably, in step 4), the neutralization process is carried out using an alkaline solution for 5-10 minutes, with an annealing temperature of 200-230°C, a holding time of 1 hour, and a slow cooling to room temperature.

[0017] Preferably, the alkaline solution is a sodium hydroxide solution with a concentration of 5-8%.

[0018] Preferably, the temperature of the drying process in steps 2) and 4) is 80-100℃ and the drying time is 30-40min.

[0019] Preferably, the preparation method further includes step 5) finished product testing: the finished panel is tested for surface touch, temperature difference resistance, scratch resistance, oil stain resistance and other properties, and after passing the test, it is packaged and put into storage.

[0020] Beneficial effects: Compared to existing technologies, the high borosilicate etched induction cooker glass panel provided by this invention uses 3mm high borosilicate glass as the substrate. Through a specific acid etching process, a uniform micro-rough structure is formed. The crystal form of this micro-rough structure is elliptical honeycomb-eye particles with a particle size of 10-30μm and a roughness controlled at 1.0-1.3μm. This results in a delicate, smooth, and warm-to-the-touch surface, solving the problem of the harsh feel of existing panels. The panel has a Mohs hardness ≥6H, excellent scratch resistance, and is not easily scratched by steel wool, knives, etc. The surface has a water contact angle ≥105° and an oil contact angle ≥90°, providing good oil resistance. Oil stains are easy to wipe clean without residue, extending the panel's lifespan. The induction cooker glass panel has a warm touch, excellent performance, is thin, and can be mass-produced. Attached Figure Description

[0021] Figure 1This is an electron microscope image of a glass panel of an induction cooker etched with high borosilicate.

[0022] Figure 2 This is an electron microscope image of the borosilicate glass in Comparative Example 3 after being etched with etching solution. Detailed Implementation

[0023] The present invention will be further described below with reference to specific embodiments, and the advantages and features of the present invention will become clearer with the description. However, unless otherwise specified, the specific experimental methods involved in the following embodiments are conventional methods or implemented according to the conditions recommended in the manufacturer's instructions.

[0024] This invention provides a high borosilicate etched induction cooker glass panel. The surface of the induction cooker glass is treated with an acid etching process to form a micro-rough structure. The crystal form of the micro-rough structure is elliptical honeycomb-eye particles, as shown in the electron microscope image. Figure 1 As shown, the elliptical honeycomb-shaped particles have a particle size of 10-30 μm. The roughness of the micro-rough structure is 1.0-1.3 μm, the gloss is 85-90%, the light transmittance is 75-80%, and the haze is 20-25%. After acid etching treatment, the induction cooker glass panel has a water contact angle ≥105°, an oil contact angle ≥90°, and a Mohs hardness ≥6H, exhibiting excellent oil resistance and scratch resistance. Oil stains are easy to wipe off, and scratches are not easily caused, extending the panel's service life.

[0025] This invention provides a method for preparing a high borosilicate etched induction cooker glass panel, comprising the following steps: 1) Substrate selection: Select 3-4mm thick high borosilicate glass as the substrate. Test the substrate's coefficient of thermal expansion, impact strength, light transmittance, and other properties to ensure compliance with requirements. Substrates with excessive thickness deviations or substandard performance will be filtered out. The substrate should meet the following requirements: coefficient of thermal expansion of 2.8 × 10⁻⁻⁻⁴. 6 / ℃ (20-300℃), flexural strength ≥65MPa, Vickers hardness ≥550HV, high temperature resistance ≥400℃, impact strength ≥120J / m², light transmittance ≥88% (unetched state). Complies with GB / T34843-2017 "Properties of Borosilicate Glass" and GB 4706.29-2023 "Safety of Household and Similar Electrical Appliances - Particular Requirements for Induction Cookers", ensuring safe use in the working environment of induction cookers.

[0026] 2) Pretreatment: The borosilicate glass substrate to be treated is cleaned, dried, and degreased to remove surface impurities and oil stains, ensuring a clean surface and avoiding affecting the etching uniformity. Specifically, the borosilicate glass substrate is placed in a cleaning solution and ultrasonically cleaned for 15 minutes to remove surface impurities. Then, it is placed in a drying device and dried at 80-100℃ for 30-40 minutes to remove surface moisture, ensuring that there is no moisture residue on the substrate surface, and avoiding moisture affecting subsequent processes and product performance. Finally, an oil remover is used to remove surface oil stains, ensuring that the substrate surface is clean, dry, and free of oil stains. 3) Preparation of etching solution: The etching solution is formulated by weight percentage as follows: hydrofluoric acid 8-12wt%, nitric acid 12-18wt%, citric acid 8-15wt%, ammonium fluoride 20-25wt%, sodium fluorosilicate 8-15wt%, starch 5-8wt%, potassium dihydrogen phosphate 1-3wt%, copper sulfate 2-6wt%, zinc chloride 2-6wt%, with the balance being water; weigh the raw materials in the formula and stir them evenly to obtain the etching solution. Place the pretreated borosilicate glass substrate into a spray etching device, adjust the etching temperature to 20-25℃, the etching time to 20-30min, and the spray pressure to 0.3-0.4MPa to ensure that the etching solution evenly covers the surface of the substrate and forms a uniform micro-rough structure. 4) Post-processing: Immerse the etched borosilicate glass substrate in pure water for 10 minutes to remove residual etching solution. Then, immerse it in a 5-8% sodium hydroxide solution for 5-10 minutes to neutralize and thoroughly remove any remaining etching solution, preventing corrosion of the panel surface. Afterward, place the substrate in a drying equipment and dry it at 80-100℃ for 30-40 minutes to remove surface moisture and ensure that there is no residual moisture on the substrate surface, preventing moisture from affecting subsequent processes and product performance. Finally, place the substrate in an annealing furnace and hold it at 200-230℃ for 1 hour, then slowly cool it to room temperature to eliminate internal stress and obtain the finished panel.

[0027] Further, in step 3), the etching solution is formulated by weight percentage as follows: hydrofluoric acid 8wt%, nitric acid 15wt%, citric acid 12wt%, ammonium fluoride 23wt%, sodium fluorosilicate 10wt%, starch 6wt%, potassium dihydrogen phosphate 2wt%, copper sulfate 4wt%, zinc chloride 2.5wt%, with the balance being water.

[0028] In this formulation, hydrofluoric acid, nitric acid, and citric acid serve as the main etching components, providing hydrogen ions to react chemically with the silicon oxide on the glass surface, thereby etching the glass surface, accelerating the etching rate, and improving etching uniformity.

[0029] Ammonium fluoride and sodium fluorosilicate, as the main etching components, provide fluoride ions to etch the glass composition framework, thereby controlling the uniformity of the etching depth and avoiding excessive etching depth. They also improve surface hardness and increase the water contact angle and oil contact angle of the glass surface. Starch, as a thickener, adjusts the viscosity of the etching solution, further improving the etching uniformity.

[0030] Dipotassium hydrogen phosphate, copper sulfate, and zinc chloride are used as additives to optimize the surface microstructure formed during the etching process, thereby improving the tactile feel and oil resistance.

[0031] Additives in the etching solution, such as copper sulfate, zinc chloride, and potassium dihydrogen phosphate, provide different metal cations that can coordinate and replace the lattice of surface particles, thereby controlling the etching speed and etching depth. Potassium dihydrogen phosphate allows the etching speed and etching depth to be achieved under controlled conditions, resulting in a more uniform and delicate frosted surface.

[0032] Furthermore, in step 3), the etching equipment is a spray etching equipment with evenly distributed spray nozzles to ensure that the etching solution uniformly covers the substrate surface, avoiding uneven etching. The preferred etching process parameters are: etching temperature 20-25℃, etching time 20-30 min, and spray pressure 0.3-0.4 MPa. These parameters were optimized through multiple orthogonal experiments to ensure etching uniformity, forming a fine micro-rough structure, while avoiding over-etching or localized lack of etching, ensuring a smooth and warm feel and stable performance of the panel surface.

[0033] Furthermore, in step 4), the neutralization process uses an alkaline solution for neutralization, with a neutralization time of 5 minutes, an annealing temperature of 200°C, a holding time of 1 hour, and a slow cooling to room temperature. This can eliminate the internal stress generated during the etching process, prevent cracks from appearing on the panel, and improve the stability and service life of the panel.

[0034] Furthermore, the alkaline solution is a sodium hydroxide solution with a concentration of 5%, which can completely neutralize the residual etching solution and prevent corrosion of the panel.

[0035] Furthermore, the preparation method also includes step 5) testing the finished panel for surface feel, roughness, gloss, light transmittance, haze, temperature difference resistance, scratch resistance, and oil resistance. Qualified products are packaged and stored; unqualified products are reworked. The finished panel has a roughness of 1.0-1.3 μm, a gloss of 85-90%, a light transmittance of 75-80%, a haze of 20-25%, a water contact angle ≥105°, an oil contact angle ≥90°, and a Mohs hardness ≥6H.

[0036] The high borosilicate etched induction cooker glass panel provided by this invention is suitable for manufacturing induction cookers. It is aesthetically pleasing, practical, and safe, providing a superior user experience and is suitable for homes and restaurants.

[0037] Example 1 A high borosilicate etched induction cooker glass panel includes a 3mm thick high borosilicate glass substrate. The surface of the high borosilicate glass substrate is treated by an acid etching process to form a micro-rough structure. The roughness of the micro-rough structure is 1.2μm, the gloss is 87%, the light transmittance is 78%, and the haze is 22%.

[0038] A method for preparing a high borosilicate etched induction cooker glass panel includes the following steps: 1) Substrate selection: High borosilicate glass was selected as the substrate. The high borosilicate glass substrate was 3mm thick and had a coefficient of thermal expansion of 2.8×10⁻⁻⁻⁶. 6 / ℃, flexural strength 68MPa, Vickers hardness 560HV, high temperature resistance 420℃, impact strength 125J / m², light transmittance 89% (unetched state), filters out those with thickness deviation exceeding ±0.1mm and coefficient of thermal expansion exceeding 3.0×10⁻ 6 Substrate with an impact strength of less than 120J / m² and a temperature of / ℃; 2) Pretreatment: Immerse the high borosilicate glass substrate in the cleaning solution and ultrasonically clean it for 15 minutes to remove surface impurities. Then, place it in the drying equipment and dry it at 80-100℃ for 30 minutes to remove surface moisture. Finally, use an oil remover to remove surface oil stains to ensure that the substrate surface is clean, dry and free of oil stains. 3) Preparation of etching solution: The etching solution is formulated by weight percentage as follows: hydrofluoric acid 8wt%, nitric acid 15wt%, citric acid 12wt%, ammonium fluoride 23wt%, sodium fluorosilicate 10wt%, starch 6wt%, potassium dihydrogen phosphate 2wt%, copper sulfate 4wt%, zinc chloride 2.5wt%, with the balance being water; weigh the raw materials in the formula and stir evenly to obtain the etching solution. Place the pretreated borosilicate glass substrate into a spray etching device, adjust the etching temperature to 20℃, the spray pressure to 0.3MPa, and etch for 25 minutes to ensure that the etching solution evenly covers the surface of the substrate and forms a uniform micro-rough structure; 4) Post-processing: Immerse the etched borosilicate glass substrate in pure water for 10 minutes to remove residual etching solution from the surface. Then, immerse it in a 5% sodium hydroxide solution for 5 minutes to neutralize and thoroughly remove residual etching solution to prevent corrosion of the panel surface. After that, place the substrate in a drying equipment and dry it at 80°C for 30 minutes to remove surface moisture. Finally, place the substrate in an annealing furnace and hold it at 200°C for 1 hour. Slowly cool it to room temperature to eliminate internal stress and obtain the finished panel.

[0039] The panel was tested and found to have a delicate, smooth, and jade-like surface with a water contact angle of 108°, an oil contact angle of 92°, and a Mohs hardness of 6H. After being placed in a -20°C environment for 2 hours and immediately transferred to a 300°C environment for 2 hours, this cycle was repeated 10 times without any cracking, deformation, or color difference. After being repeatedly rubbed with a steel wool pad 500 times, no obvious scratches were found on the surface. When cooking oil was dripped onto the surface and left to stand for 24 hours, it was wiped clean with water, leaving no oil residue. The heat transfer efficiency showed no significant decrease compared to ordinary panels, meeting the requirements for use with induction cookers.

[0040] Example 2 A method for preparing a 3mm high borosilicate etched induction cooker glass panel includes the following steps: Substrate selection: 3mm thick high borosilicate glass was selected as the substrate. The substrate's coefficient of thermal expansion, impact strength, and light transmittance were tested. Substrate with a thickness deviation exceeding ±0.1mm and a coefficient of thermal expansion exceeding 3.0×10⁻⁻⁻⁶ was rejected. 6 Substrate with an impact strength of less than 120J / m² and a temperature of / ℃; Pretreatment: Place the screened substrate into an ultrasonic cleaner, add cleaning solution (deionized water + 0.5% detergent), and ultrasonically clean for 20 minutes to remove surface impurities; then place it in a drying oven and dry at 90℃ for 30 minutes to remove surface moisture; finally wipe the surface with alcohol to remove oil stains, ensuring that the substrate surface is clean, dry, and free of oil stains. 3. Acid etching: Prepare the etching solution by weight percentage: hydrofluoric acid 10wt%, nitric acid 16wt%, citric acid 10wt%, ammonium fluoride 25wt%, sodium fluorosilicate 8wt%, starch 5wt%, potassium dihydrogen phosphate 3wt%, copper sulfate 5wt%, zinc chloride 2wt%, and the balance is water.

[0041] The pretreated substrate was placed in a spray etching equipment, the etching temperature was adjusted to 20℃, the spray pressure was adjusted to 0.3MPa, and the etching time was 25 minutes. 4. Post-treatment: Immerse the etched substrate in deionized water for 30 minutes to remove residual etching solution; then immerse it in a 5% sodium hydroxide solution for 5 minutes to neutralize and thoroughly remove residual etching solution; next, place the substrate in a drying oven and dry at 90℃ for 30 minutes to remove surface moisture; finally, place the substrate in an annealing furnace and hold at 200℃ for 1 hour, then slowly cool it to room temperature at a rate of 5℃ / min to eliminate internal stress. 5. Finished Product Inspection: The finished panels are tested for surface feel, roughness, gloss, light transmittance, haze, temperature difference resistance, scratch resistance, and oil resistance. Qualified products are packaged and put into storage, while unqualified products are reworked.

[0042] A total of 100 finished products were produced in this batch. After testing, the pass rate was 97%. All qualified products met the performance requirements of this invention. The process is stable and controllable, and can be mass-produced.

[0043] Comparative Example 1 An induction cooker glass panel, made of 4mm thick ordinary tempered glass, without acid etching treatment, and with other conditions consistent with Example 1. Testing revealed that the panel has a stiff feel and a coefficient of thermal expansion of 4.5 × 10⁻⁻⁻⁴. 6 / ℃, poor temperature resistance, cracks appear after 3 cycles of temperature difference from -20℃ to 300℃; Mohs hardness 5H, obvious scratches appear after 200 cycles of steel wool friction; water contact angle 85°, oil contact angle 75°, oil stains are easy to leave residue and difficult to wipe, performance is far lower than the product of this invention.

[0044] Comparative Example 2 An induction cooker glass panel is made of 3mm thick high borosilicate glass and etched using a conventional etching solution (20wt% hydrofluoric acid, 10wt% nitric acid, and the balance water). The etching parameters are an etching temperature of 25℃ and an etching time of 20min, with other conditions consistent with Example 1. Testing revealed uneven etching on the panel surface, a roughness of 1.8μm, a rough feel, and obvious scratches; a Mohs hardness of 5H, indicating insufficient scratch resistance; and a water contact angle of 95°, indicating poor oil resistance, failing to meet the performance requirements of this invention.

[0045] Comparative Example 3 A high borosilicate glass was prepared using the etching solution and experimental conditions described in Example 1 of the background art (CN 111362584 A).

[0046] Comparison of performance parameters of high borosilicate glass before and after etching in the above embodiments By comparing Examples 1 and 2 with Comparative Examples 1, 2 and 3, it can be seen that the 3mm high borosilicate etched induction cooker glass panel of the present invention, through reasonable material selection, optimized etching solution formula and process parameters, solves the technical pain points of existing panels, and has the advantages of excellent touch, stable performance, thinness and mass production capability, and has high practicality and market value.

[0047] The present invention has the following beneficial effects: 1. Excellent tactile feel: This invention uses 3mm high borosilicate glass as the substrate and is treated with a specific acid etching process to form a uniform micro-rough structure with a roughness controlled between 1.0-1.3μm. This gives the panel surface a delicate, smooth, and warm jade-like feel, solving the problem of the stiff feel of existing panels and improving the user experience. At the same time, the gloss, light transmittance, and haze are controlled within a reasonable range, taking into account both aesthetics and practicality.

[0048] 2. Excellent performance: The high borosilicate glass substrate has a low coefficient of thermal expansion (2.8×10⁻⁻⁻⁴).6 (℃), high temperature resistance ≥400℃, can withstand sudden temperature changes from -20℃ to 300℃, excellent temperature difference resistance, far exceeding the requirements of GB / T34843-2017, can adapt to the working scenario of sudden heating when the induction cooker is turned on and sudden cooling when it is turned off, avoiding problems such as cracking and deformation; the panel has a Mohs hardness ≥6H, excellent scratch resistance, and is not easily scratched by steel wool, knives, etc.; the surface water contact angle ≥105°, oil contact angle ≥90°, good oil stain resistance, oil stains are easy to wipe without residue, extending the service life of the panel.

[0049] 3. Thin design: It adopts 3mm thick high borosilicate glass, which is lighter and more adaptable than the existing 4-5mm thick panels. It can meet the development needs of thin and lightweight mid-to-high-end induction cookers, without affecting the strength and heat conduction efficiency of the panel.

[0050] 4. Stable process and scalable mass production: This invention optimizes and determines the etching solution formula and process parameters, resulting in a stable and controllable process with high etching efficiency and a product qualification rate of ≥98.5%. At the same time, by optimizing the etching solution recycling process, production costs are reduced by about 10%, enabling scalable mass production to meet market supply demands and achieving high economic benefits.

[0051] 5. The preparation method is simple and easy to implement: The preparation method of the present invention has clear steps and is easy to operate. It does not require complicated equipment and processes, making it easy to promote and apply. At the same time, through pretreatment and posttreatment processes, the product performance is ensured to be stable and the defect rate is reduced.

[0052] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several changes and improvements without departing from the overall concept of the present invention, and these should also be considered within the scope of protection of the present invention.

Claims

1. A high borosilicate etched induction cooker glass panel, characterized in that, The glass surface of the induction cooker is treated with an acid etching process to form a micro-rough structure, and the crystal form of the micro-rough structure is elliptical honeycomb-eye particles.

2. The high borosilicate etched induction cooker glass panel according to claim 1, characterized in that, The elliptical bee-eye particles have a particle size of 10-30 μm.

3. A method for preparing a high borosilicate etched induction cooker glass panel as described in claim 1 or 2, characterized in that, Includes the following steps: 1) Substrate selection: High borosilicate glass was selected as the substrate; 2) Pretreatment: The borosilicate glass substrate to be treated is cleaned, dried, and degreased; 3) Preparation of etching solution: The etching solution is formulated by weight percentage as follows: hydrofluoric acid 8-12wt%, nitric acid 12-18wt%, citric acid 8-15wt%, ammonium fluoride 20-25wt%, sodium fluorosilicate 8-15wt%, starch 5-8wt%, potassium dihydrogen phosphate 1-3wt%, copper sulfate 2-6wt%, zinc chloride 2-6wt%, with the balance being water; weigh the raw materials in the formula and stir them evenly to obtain the etching solution, then place the pretreated borosilicate glass substrate into the etching equipment for etching; 4) Post-processing: The etched borosilicate glass substrate is cleaned and neutralized to remove residual etching solution from the surface, and then dried and annealed to obtain the finished panel.

4. The method for preparing a high borosilicate etched induction cooker glass panel according to claim 3, characterized in that, The borosilicate glass substrate mentioned in step 1) has a thickness of 3-4 mm and a coefficient of thermal expansion of 2.8 × 10⁻⁻⁻⁶. 6 / ℃ (20-300℃), flexural strength ≥65MPa, Vickers hardness ≥550HV, high temperature resistance ≥400℃, impact strength ≥120J / m², light transmittance ≥88%.

5. The method for preparing a high borosilicate etched induction cooker glass panel according to claim 3, characterized in that, The etching solution is formulated by weight percentage as follows: hydrofluoric acid 8wt%, nitric acid 15wt%, citric acid 12wt%, ammonium fluoride 23wt%, sodium fluorosilicate 10wt%, starch 6wt%, potassium dihydrogen phosphate 2wt%, copper sulfate 4wt%, zinc chloride 2.5wt%, with the balance being water.

6. The method for preparing a high borosilicate etched induction cooker glass panel according to claim 3, characterized in that, The etching equipment mentioned in step 3) is a spray etching equipment, and the etching process parameters are: etching temperature 20-25℃, etching time 20-30min, and spray pressure 0.3-0.4MPa.

7. The method for preparing a high borosilicate etched induction cooker glass panel according to claim 3, characterized in that, In step 4), the neutralization process is carried out using an alkaline solution for 5-10 minutes, with an annealing temperature of 200-230℃, a holding time of 1 hour, and a slow cooling to room temperature.

8. The method for preparing a high borosilicate etched induction cooker glass panel according to claim 7, characterized in that, The alkaline solution is a sodium hydroxide solution with a concentration of 5-8%.

9. The method for preparing a high borosilicate etched induction cooker glass panel according to claim 3, characterized in that, The temperature of the drying process in steps 2) and 4) is 80-100℃, and the drying time is 30-40min.

10. The method for preparing a high borosilicate etched induction cooker glass panel according to claim 3, characterized in that, The preparation method also includes step 5) finished product testing: the finished panel is tested for surface touch, temperature difference resistance, scratch resistance, oil stain resistance and other properties, and after passing the test, it is packaged and put into storage.

Citation Information

Patent Citations

  • High borosilicate glass etching solution and preparation method and application thereof

    CN111362584A